Single-channel properties and regulation of Chloride Intracellular Channel proteins - Singh, Harpreet (The University of Edinburgh, 2007)
Chloride Intracellular Channel (CLIC) proteins are ubiquitous in multicellular organisms and often coexist in soluble and integral membrane forms. They can autoinsert into membranes to form molecular components of intracellular ion channels. Soluble CLICs are structurally similar to Q-type glutathione-S-transferases (GSTs), but the structure of the membrane proteins remains elusive.

In this study, soluble, recombinant, human CLIC1, rat brain CLIC4 (p64Hl) and human CL1C5A, a splice variant of p64 (CLIC5B), were expressed as cleavable Histagged proteins and incorporated into voltage-clamped planar lipid bilayers. They inserted spontaneously with or without an intact His-tag to form redox-regulated ion channels. All showed well-defined sublevels with similar reversal potentials and ionic selectivities. Redox titration in vitro using a glutathione coupled buffer system led to a sequential reduction in conductance as oxidation progressed on the extracellular or "luminal" side. These changes were fully reversible, suggesting that intracellular redox potential may play a role in modulating CLIC channel activity. The channels were sensitive to the cysteine-reactive compounds NEM and DTNB. Furthermore, CLIC1 and CLIC4 activity was inhibited by their respective affinitypurified antibodies.

The putative pore forming region was identified based on previous work and CLIC channels appear to contain at least 4 subunits each with a single transmembrane domain (TMD). In this simple model, the luminal side of each subunit contains a single cysteine residue located just before the putative pore entrance. Consistent with these ideas, truncated proteins comprising the first 58 residues of CLIC1, or the first xxiii 61 residues of CLIC4 (sufficient in each case to contain the putative TMD), autoinserted into bilayers to form redox-sensitive ion channels and could be blocked by cysteine reactive compounds applied from the luminal side. The truncated proteins showed reduced conductances, and were non-selective between anions and cations.

CLIC5A was originally identified in an ezrin-containing cytoskeletal complex. The hypothesis that actin regulates the channel activity of CLICs was tested. Actin polymerisation on the cytosolic side (but not the luminal side) led to near-complete channel closure, restricting openings to minor substate levels of CLIC1 and CLIC5A (there was no effect on CTIC4). Addition of actin-destabilising agents such as latrunculin B and cytochalasin B inhibited or reversed the effect. CLIC1 also colocalised with F-actin in both HEK-293 cells and neuroblastoma cells (N2a). These studies indicated that CLIC5A and CL1C1 channel function may be regulated by the cortical actin cytoskeleton, providing a new mechanism to regulate localised ion flux in cells. Unusually, the interaction may be direct, without any intermediate or adapter protein.

CLICs also interact with dynamin I and cytoskeletal proteins in vitro. Additional in vitro studies were carried to map the CLIC binding site to the proline-rich domain (PRD) of dynamin I. This interaction also occurs in vivo, since dynamin 1 and CLICs form a complex in nerve terminals as previously shown by co-immunoprecipitation. In agreement, immunofluorescence studies in rat cerebellar granule cells showed significant co-localization between dynamin I and CLICs. The CLIC proteins showed distinct sub cellular localizations. CLIC1 and CLIC4 are also localised in xxiv nerve terminals as shown by co-localization with the synaptic vesicle (SV) marker synaptophysin. The localisation of CLICs in nerve terminals and their interaction with dynamin suggests a possible role in SV recycling.

In summary, CLICs can form poorly-selective, oligomeric ion channels modulated by luminal GSH-dependent transthiolation and in some cases by actin polymerisation from the cytosolic side. The transmembrane domain can autoinsert, but is not enough to form channels identical to wild-type channels. These preliminary structurefunction studies have provided an overview of the molecular mechanism of membrane CLICs. Discovery of regulatory mechanisms for CLICs may shed more light on their functional roles in cells during processes such as the cell cycle and apoptosis.